PENGARUH TEMPERATUR TUANG DENGAN JENIS MATERIAL Al PADUAN (RONGSOK WAJAN) TERHADAP KEKERASAN HASIL PENGECORAN EVAPORATIVE - Taufiq Hidayat; Mastiadi Tamjidillah (Scientific Journal of Mechanical Engineering Kinematika, 2016)
The objective of this research is to know the effect of casting temperature with the kind of guide material AI alloy junk from pan on hardness (the evaporative foundry result). The recycling of used aluminum is an alternative to reduce the waste material from aluminum. Recycling is a way of processing used materials that is started with selection, collection, then the process of foundry to create a new product that is more valuable economical. Casting temperature is an variable that can effect the result of foundry where if the casting temperature is low, then there will be a quick freeze before the mold is completely filled. And if the casting temperature is too high, then shrinkage can occur anditheiporosity value may increase. This research used four casting temperature variations, namely: 650°C, 700°C, 750°C, and 800°C. The evaporative foundry method uses styrofoam pattern that is piled up into sand mold. The metal that is casted will form like styrofoam pattern. The resultiof casting temperature testing can effect on hardness.